(untitled) (Quinto Sol, 2023)
This article analyzed the application of the law of agricultural centers of 1887 in the Buenos Aires province. For this, the agricultural center La Constancia, in the Ayacucho district, located in the southeast of the provincial territory, was taken as the object of the investigation. Through the interweaving of various sources and the approach to the existing bibliography on the subject, an attempt was made to account for the details of its implementation in a case in which, contrary to what happened at a general level, it was possible to achieve, in the early years, some objectives of the law linked to the distribution of land, the development of agricultural production and the settlement of population in rural areas. Although the center was dismantled as such at the end of 1894, as a result of the general lack of success of the law and the economic crisis that the province and its banking institutions were going through, the population settled in the area remained and shaped a community that at the beginning of the 20th century it was thriving and it still remains today, although reduced to a minimum expression. Although, the center was dismantled as such late 1894, product of the limited general success of the law and the economic crisis that the province and banking institutions were going through, the settled population in the area remained, giving shape to a community that at the beginning of the XX century, it was strong and remains even today, although reduce to a minimal expression.